2001
DOI: 10.2208/prohe.45.373
|View full text |Cite
|
Sign up to set email alerts
|

Movable Bed Scour Around Submerged Spur-Dikes

Abstract: This paper presents the results of an exploratory study on scour occurring around submerged spur-dike. The effect of flow depth and spur-dike dimensions was studied with the help of the experimental data. It was found that the overtopping ratio and the opening ratio are significantly affected on the maximum scour depth. The larger opening ratios (a) caused relatively small scour area and the bank erosion downstream the spur-dike hardly can occur. The longer spur-dike length & the lower flow depth produced scou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 15 publications
1
12
1
Order By: Relevance
“…12.). The observed scouring during the surge was different from what was described earlier by Elawady et al 3) and what was observed in the authors' former research for the case of a stable flow. For the stable flow, the scouring was very intense at the beginning, and then gradually became weaker.…”
Section: Final Scour Depthcontrasting
confidence: 98%
See 1 more Smart Citation
“…12.). The observed scouring during the surge was different from what was described earlier by Elawady et al 3) and what was observed in the authors' former research for the case of a stable flow. For the stable flow, the scouring was very intense at the beginning, and then gradually became weaker.…”
Section: Final Scour Depthcontrasting
confidence: 98%
“…Following this assumption much research work was done on the interaction between velocity profiles and scouring near the obstacle. This main parameter was studied in an experimental manner by Ishigaki2), Elawady et al 3) and others. The influence of spur dike geometry, its inclination in a channel and the overtopping ratio, was investigated by many scientists such as Bahar and Fukuoka4) and Elawady et al3).…”
Section: Introductionmentioning
confidence: 99%
“…At low relative submergence levels (i.e., when the ratio of main channel depth to the protruding obstruction height is small), the flow field near the water surface nearly parallels the main channel flow during an overtopping event and then returns to an emergent lateral cavity flow field between events (Uijttewaal, 2005). At higher submergence levels, the near-surface cavity flow remains nearly parallel to the main channel flow (Elawady et al, 2000;Uijttewaal, 2005;Yossef and De Vriend, 2011). The middepth and deeper regions of the recirculating flow are largely unaffected because the deeper cavity flow is driven by momentum exchange through the lateral mixing layer (Peng and Kawahara, 1997;Peng et al, 1999;McCoy et al, 2007).…”
Section: Submerged Lateral Cavitiesmentioning
confidence: 99%
“…Most of previous experiments on ow eld around the spur dike were conducted to investigate the mean and turbulent parameters [1][2][3][4][5][6][7][8][9][10]. Chen and Ikeda [1] and Yossef [4] studied the ow pattern of emerged spur dikes and separated the ow elds into four main regions: main ow zone, return ow zone, shear layer, and reattachment point.…”
Section: Introductionmentioning
confidence: 99%
“…Chen and Ikeda [1] and Yossef [4] studied the ow pattern of emerged spur dikes and separated the ow elds into four main regions: main ow zone, return ow zone, shear layer, and reattachment point. Elawady et al [2,3] studied the qualitative nature of the ow eld around a submerged spur dike. According to this research, the fully submerged and just submerged spur dike ow elds are completely di erent, and the downstream recirculation region length depends on the spur dike's shape and height.…”
Section: Introductionmentioning
confidence: 99%